Early liver metastases after "failure" of adjuvant chemotherapy for stage III colorectal cancer: is there a role for additional adjuvant therapy?. Issue 4 (April 2021) - Boerner, Thomas; Zambirinis, Constantinos; Gagnière, Johan; Chou, Joanne F.; Gonen, Mithat; Kemeny, Nancy E.; Cercek, Andrea; Connell, Louise C.; Kingham, Thomas P.; Allen, Peter J.; Balachandran, Vinod P.; Drebin, Jeffrey; et al.
Abstract: Background: The utility of adjuvant chemotherapy after resection of colorectal liver metastasis (CLM) in patients with rapid recurrence after adjuvant chemotherapy for their primary tumor is unclear. The aim of this study was to evaluate the oncologic benefit of adjuvant hepatic arterial plus systemic chemotherapy (HAIC + Sys) in patients with early CLM. Methods: A retrospective analysis of patients with early CLM (≤12 months of adjuvant chemotherapy for primary tumor) who received either HAIC + Sys, adjuvant systemic chemotherapy alone (Sys), or active surveillance (Surgery alone) following resection of CLM was performed. Recurrence and survival were compared between treatment groups using Kaplan–Meier methods and Cox proportional hazards models. Results: Of 239 patients undergoing resection of early CLM, 79 (33.1%) received HAIC + Sys, 77 (32.2%) received Sys, and 83 (34.7%) had Surgery alone. HAIC + Sys was independently associated with reduced risk of RFS events (adjusted hazard ratio [HRadj]: 0.64, 95%CI:0.44–0.94, p  = 0.022) and all-cause mortality (HRadj: 0.54, 95%CI:0.36–0.81, p  = 0.003) compared to Surgery alone patients. Largest tumor >5 cm (HRadj: 2.03, 95%CI: 1.41–2.93, p  < 0.001) and right-sided colon tumors (HRadj: 1.93, 95%CI: 1.29–2.89, p  = 0.002) were independently associated with worse OS. Conclusion: Adjuvant HAIC + Sys after resection of early CLM that occur after chemotherapy for node-positive primary is associated with improved outcomes.